Prejudice And Stereotype Reflected In William Shakespeare's Much Ado About Nothing (1600) : A Social Psychological Perspective - Firda., Atina Rahmawati; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
The major problem of this study is how prejudice and stereotypes are reflected in Much Ado About Nothing play. The objectives of this study is to analyze the play based on the structural elements and based on social psychological perspective. The research uses qualitative research. The data of the research consists of primary data and secondary data. The primary data of the research is Much Ado About Nothing drama and the secondary data of the research are other materials related of the study. Technique of data collecting is the library research the steps are: reading some books and articles, accessing internet, taking note important parts in both the primary data and secondary data, and arranging the data into several categories. In analyzing the data, the researcher employs descriptive qualitative method. The result of the study shows the following conclusion. Based on the social psychological perspective analysis, William Shakespeare illustrates that people tend to have prejudice and build stereotypes to others and Shakespeare presents a psychological phenomenon in which people often consider other people as the "others" who are different from them. William Shakespeare wants to show that consciously or unconsciously prejudice and stereotypes are common in our lives.